Inclusive Schools and Violence: Investigating the Role of Acceptance and Student Participation - Mirnawati Mirnawati; Amka Amka; Dewi Juwita Susanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the relationship between social acceptance, the inclusion of students with special needs, and the incidence of violence in inclusive schools. The objective is to determine how these factors interact and influence the well-being of learners with special needs in inclusive educational settings. A quantitative, correlational survey design was employed. Data were collected from students with special needs enrolled in inclusive schools across Banjarmasin City. Instruments included structured questionnaires and interviews, utilizing a Likert scale to assess levels of social acceptance, participation in academic and non-academic activities, and the frequency of experienced violence. Validity was established through expert judgment, and reliability was confirmed using Cronbach's Alpha. Pearson correlation analysis was conducted to explore bivariate relationships, and multiple linear regression was used to assess the interaction between variables. The analysis revealed a significant negative correlation between social acceptance and violence (r = -0.56, p 0.01), indicating that higher levels of social acceptance are associated with reduced violence. Additionally, the inclusion of students with special needs was positively correlated with a reduction in violence (r = 0.47, p 0.05). The combined effect of social acceptance and inclusion accounted for 71% of the variance in violence reduction (R² = 0.71), suggesting a strong predictive interaction. The findings underscore the critical role of fostering social acceptance and inclusive practices to minimize violence and create a safer, more supportive school environment for students with special needs.